THE DEVELOPMENT OF A WRITTEN ESSAY GUIDE BASED ON GO TO YOUR POST IN 5TH GRADE ELEMENTARY SCHOOL STUDENTS - Hafni Kharismawati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to develop a guidebook for writing descriptive essays. The research employed a Research and Development (R&D) method using the Borg and Gall design as modified by Sugiyono. The development resulted in a descriptive essay writing guidebook based on the Go To Your Post approach. The feasibility test conducted by media experts indicated that the guidebook was feasible, with an average score of 79%. Validation by material experts showed that the product was highly feasible, obtaining an average score of 87.31%. Furthermore, validation by linguists demonstrated that the guidebook was appropriate, with an average score of 76%. The results of the student response questionnaire in a limited trial obtained an average score of 92%, categorized as very good. Based on these findings, the final product of the descriptive essay writing guidebook based on Go To Your Post is considered suitable for use in learning activities for fifth-grade elementary school students.